Covid 19 Pandemic Mitigation in Indonesia - Zeffry Alkatiri (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2021)
Reviewing Mas`udi, W. & Winanti., P. W. (2020). Tata Kelola Penanganan COVID-19 di Indonesia: Kajian Awal. Yogyakarta: Gajah Mada University Press.